Excavating cultural imperialism in student mobility programmes. Issue 4 (4th July 2018) - Manathunga, Catherine
ABSTRACT: The New Colombo Plan and similar student mobility initiatives in Aotearoa/New Zealand have been pitched as reversing the culturally imperialist focus of the original Colombo Plan (CP) because they involve sending Australian and Aotearoa/New Zealand students to the Indo-Pacific region instead of funding Asian students to study overseas. However, changes in this direction of student mobility mask ongoing geopolitical inequities. In order to interrogate these subtle power relations, this article adopts a Foucauldian genealogical approach. It briefly outlines the competing goals of the original CP before undertaking an analysis of the discourses evident in the Australian government's New Colombo Plan and in the Education New Zealand's Prime Minister's Scholarship for Asia. This discourse analysis illustrates the extent to which the new student mobility programmes established in Australia and Aotearoa/New Zealand involve consuming the 'Indo-Pacific' and 'Asian' Other and often serves to reinforce rather than address global geopolitical inequities.